(untitled) (Swiss Medical Weekly, 2016)
INTRODUCTION: Smoking bans are considered one of the most effective policies to reduce population exposure to tobacco smoke and prevent adverse health outcomes. However, evidence on the effect of contextual variables on the effectiveness of smoking bans is still lacking. AIMS: The patchwork of cantonal smoke-free laws in Switzerland was used as a quasi-experimental setting to assess changes after their introduction in: hospitalisations and mortality due to cardiorespiratory diseases in adults; total hospitalisations and hospitalisations due to respiratory disorders in children; and the modifying effects of contextual factors and the effectiveness of the laws. METHODS: Using hospital and mortality registry data for residents in Switzerland (2005–2012), we conducted canton-specific interrupted time-series analyses followed by random effects meta-analyses to obtain nationwide smoking ban estimates by subgroups of age, sex and causes of hospitalisation or death. Heterogeneity of the impact caused by strictness of the ban and other smoking-related characteristics of the cantons was explored through meta-regression. RESULTS: Total hospitalisation rates due to cardiovascular and respiratory diseases did not significantly change after the introduction of the ban. Post-ban changes were detected in ischaemic heart disease hospitalisations, with a 2.5% reduction (95% confidence interval [CI)] −6.2 to 1.3%) for all ages and 5.5% (95% CI −10.8 to −0.2%) in adults 35–64 years old. Total mortality due to respiratory diseases decreased by 8.2% (95% CI −15.2 to −0.6%) over all ages, and chronic obstructive pulmonary disease mortality decreased by 14.0% (95% CI −22.3 to −4.5%) in adults ≥65 years old. Cardiovascular mortality did not change after the introduction of the ban, but there was an indication of post-ban reductions in mortality due to hypertensive disorders (−5.4%, 95% CI −12.6 to 2.3%), and congestive heart failure (−6.0%, 95% CI −14.5 to 3.4%). No benefits were observed for hospitalisations due to respiratory diseases in children or for infant mortality. The type of smoking ban implemented explained the heterogeneity of benefits across cantons for some outcomes. CONCLUSION: Smoking bans in Switzerland were associated with overall reductions in cardiovascular and respiratory hospitalisation and mortality in adults.